2022
DOI: 10.1111/papr.13099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erector spinae plane block on postoperative analgesia after pediatric hip surgery: Randomized controlled study

Abstract: Background Erector spinae plane block (ESPB) in pediatric patients presenting for hip surgery may improve the postoperative analgesia. Aim The study aimed to investigate the effect of ultrasound‐guided ESPB on postoperative analgesia after a pediatric hip surgery. Methods Forty children scheduled for hip surgeries were included in this trial and randomly distributed into; Control group, patients received sham ultrasound‐guided ESPB at the level of L3 or ESPB group, patients received real ultrasound‐guided ESPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…[ 16 ] concluded that ESP block was an effective analgesic block for open paediatric midline splenectomy with lower postoperative pain scores and intraoperative fentanyl intake. Following Abduallah et al .’s results,[ 17 ] this study recorded that ESP blocks for paediatric hip surgeries could result in a longer first request for postoperative analgesia, minimising intraoperative fentanyl and postoperative morphine consumption and pain measurements. This research did not observe a change in the frequency of adverse effects and the level of parental satisfaction.…”
Section: Discussionmentioning
confidence: 93%
“…[ 16 ] concluded that ESP block was an effective analgesic block for open paediatric midline splenectomy with lower postoperative pain scores and intraoperative fentanyl intake. Following Abduallah et al .’s results,[ 17 ] this study recorded that ESP blocks for paediatric hip surgeries could result in a longer first request for postoperative analgesia, minimising intraoperative fentanyl and postoperative morphine consumption and pain measurements. This research did not observe a change in the frequency of adverse effects and the level of parental satisfaction.…”
Section: Discussionmentioning
confidence: 93%